PEMANFAATAN MEDIA SOSIAL (WHATSAPPS) SEBAGAI SARANA PEMBERIAN INFORMASI KESEHATAN REPRODUKSI REMAJA SEKOLAH DI SMU 1 LAWANG - Handy Lala (Jurnal Informasi Kesehatan Indonesia (JIKI), 2020)
The development of the fast-paced Internet and information traffic world has created very new opportunities for young people to interact with others or find information. Information from the internet is far more interesting and memorable so that it will have a stronger influence on young people. The purpose of this study is to provide reproductive health information through social media whatsapps to high school level adolescents. This study uses a qualitative method with a phenomenological approach. The research subjects were high school students. Data collection was carried out through in-depth interviews, FGDs and observations. The results of this study are the provision of reproductive health information through social media whatapps provides a lot of valuable information to students including easy access, can be read repeatedly, updates and updates, consulting activities can be directly interactive with the admin so that students do not feel bored and bored. The conclusion of this research is the program of providing reproductive health information through social media WhatsApp has a very positive impact on school students